Evaluation of an integrated group cognitive-behavioral treatment for comorbid mood, anxiety, and substance use disorders: A pilot study. (March 2017) - Milosevic, Irena; Chudzik, Susan M.; Boyd, Susan; McCabe, Randi E.
Highlights: We developed an integrated group CBT for comorbid mood, anxiety, and substance use disorders. The treatment was evaluated in an uncontrolled pilot effectiveness study. Treatment may reduce stress and alcohol use symptoms and improve substance refusal self-efficacy. Overall clinical significance of change across depression, anxiety, and substance use was modest. Methodological and sample size limitations warrant more rigorous treatment evaluation. Abstract: This paper presents the development and preliminary evaluation of an integrated group cognitive-behavioral treatment (CBT) for comorbid mood, anxiety, and substance use disorders. The 12-session, manualized treatment was developed collaboratively by a mental health program in a teaching hospital and a community-based addictions service and administered in both settings. Results from an uncontrolled effectiveness trial of 29 treatment completers suggest that integrated group CBT may reduce stress and alcohol use symptoms and improve substance refusal self-efficacy. Changes in symptoms of anxiety, depression, and drug use were not significant, although the effect size for anxiety reduction was in the medium range. Nonetheless, the clinical significance of treatment effects on mood, anxiety, and substance use symptoms was modest. Changes in coping skills and quality of life were not significant, although medium-to-large effects were observed for changes in several coping skills. Participants reported being highly satisfied with treatment, found the treatment strategies to be useful, and noted an improvement in their functioning, particularly socially. Methodological and sample size limitations warrant more rigorous follow-up investigations of this treatment. Results are considered in the context of the current literature on integrated psychological treatments for these common comorbidities.